Landscape ecological risk assessment and driving factors analysis based on optimal spatial scales in Luan River Basin, China - Nijuan Yang; Ting Zhang; Jianzhu Li; Ping Feng; Nina Yang (Ecological Indicators)
Rapid urbanization and human activities have significantly influenced landscape ecological pattern and increased ecological risk. Landscape ecological risk (LER) assessment serves as an effective tool to capture the effects of natural evolution and human activities on ecosystems comprehensively, but the assessment result is subject to spatial scales. This paper figured out the optimal spatial scales of the Luan River Basin integrating response curves, area accuracy loss model, and semi-variation function under the appropriate resampling method. The improved landscape ecological risk index (ILERI) model was established to assess LER based on optimal spatial scales, employing spatial autocorrelation theory and Geodetector to reveal the spatio-temporal traits and influencing factors of LER. The results showed: (1) Nearest is the appropriate raster resampling method in landscape pattern analysis of Luan River Basin, and the optimal spatial granularity and amplitude are 30 m and 3200 m, respectively; (2) In 2000, 2008, 2016 and 2022, ILERI was 0.242, 0.249, 0.250 and 0.234, respectively, and LER levels were medium–low and medium predominantly, which accounted for 64.87 %, 52.28 %, 68.76 % and 70.55 %; (3) Recent data showed a decline in LER levels, with higher risks concentrated in the northwest and lower risks in the southeast. Precipitation, population density, and primary industry were the primary factors and the interaction of multiple factors played a more significant role. This study will provide reference for planning land use and managing ecological environment in the Luan River Basin.